Force of habit [large type] - Loweecey, Alice (Loweecey, Alice. Falcone & Driscoll investigation., 2011)
Giulia Falcone is convinced she's going to Hell. First, she left the convent. Second, her new job with a private investigator has her sneaking around and lying. Adjusting to life in the outside world isn't easy. Despite a crush on her boss, a foul-mouthed, soft-hearted ex-cop, she's sure he'd never fall for an ex-nun. And her first case, which involves wealthy, drop-dead handsome Blake Parker, draws Giulia into a stalker's twisted game and a fight for her life.